2015
DOI: 10.3201/eid2106.150013
|View full text |Cite
|
Sign up to set email alerts
|

Ebola Risk Perception in Germany, 2014

Abstract: Knowledge about actual risks was poor, creating the potential for inappropriate behavior changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
49
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 17 publications
6
49
0
2
Order By: Relevance
“…There are other studies, which investigated Ebola risk perceptions, Ebola knowledge and the prevention of the Ebola virus during the last Ebola outbreak in West Africa [2226]. However, the populations of these studies were objectively at lower risk of contracting Ebola than the population assessed in this study.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…There are other studies, which investigated Ebola risk perceptions, Ebola knowledge and the prevention of the Ebola virus during the last Ebola outbreak in West Africa [2226]. However, the populations of these studies were objectively at lower risk of contracting Ebola than the population assessed in this study.…”
Section: Discussionmentioning
confidence: 78%
“…A study about Ebola risk perceptions in Germany [22] also found that most of their study participants would change their behaviour in order to prevent an outbreak of the Ebola virus. The majority of the respondents in this study has access to a mobile phone in their household.…”
Section: Discussionmentioning
confidence: 99%
“…6 Similar results were reported from studies in Germany as well as others from Liberia and Sierra Leone. 18,20,22 A majority also thought that the disease is airborne, the same misconception was also the case among other respondents in Nigeria, Sierra Leone and Germany. 15,18,22 This shows that a further understanding of the difference between air borne and aerosol transmission is needed as although they may be similar to the layman, it is necessary for HCW to correctly identify this.…”
Section: Discussionmentioning
confidence: 94%
“…18,20,22 A majority also thought that the disease is airborne, the same misconception was also the case among other respondents in Nigeria, Sierra Leone and Germany. 15,18,22 This shows that a further understanding of the difference between air borne and aerosol transmission is needed as although they may be similar to the layman, it is necessary for HCW to correctly identify this. 7 Fever and bleeding were popular signs and symptoms among respondents, this correlates with a study in Nigeria.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation